Instilling Moral Character Education and Student Discipline through Extracurricular Programs at SMASK Alvarez Paga - Maria Rosalinda Daro; Danar Aswim; M. Ihsan Wahab (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
Education can help students to think critically about problems that occur in society, school and family. However, on the other hand, it helps students to become individuals with character wherever they are. Therefore, formal and informal education have a very important role in the process of educating students and supporting the development of student personality. This study aims to determine the instillation of morality and discipline character education through extracurricular programs at SMASK Alvarez Paga and to determine the morality and discipline of SMASK Alvarez Paga students through extracurricular programs. The research method used is qualitative research with a descriptive approach. The research subjects involved were the principal, BK teachers, extracurricular activity supervisors and students. The data collection methods used were observation, interviews and documentation. Based on the results of this study, the researcher concluded that the instillation of moral character education and discipline through extracurricular programs can be done by means of a coaching pattern in the form of Scouts, Sports and Arts. This instillation must continue to be carried out in accordance with the curriculum and the school's superior programs, and the development of morality and discipline of students is very important to realize students with noble character, high morals, hard work, work discipline, tolerance and responsibility.